2020
DOI: 10.1177/0218492320933442
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Society for Cardiac Surgeons consensus document on COVID-19, April 1, 2020

Abstract: The COVID-19 pandemic represents an international health crisis that is challenging to all governments. Health practitioners in different fields have a duty to guide people and governments to achieve safe health practices. The Saudi Society for Cardiac Surgeons recognizes that it is difficult to establish evidence-based guidelines for safe cardiac surgery practices in such a crisis because this is an unprecedented health pandemic. So we decided to work with our colleagues in other societies by reviewing differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In contrast, Haft et al [ 4 ] proposed a tiered patient triage guidance statement, as shown in Table 1 . A similar triage and prioritization system was published by the Saudi Society for Cardiac Surgeons [ 5 ]. Meanwhile, Hussain et al [ 6 ] suggested a service system for providing urgent and emergency cardiac surgery for all of London, focusing on maintaining a Covid-free in-hospital environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Haft et al [ 4 ] proposed a tiered patient triage guidance statement, as shown in Table 1 . A similar triage and prioritization system was published by the Saudi Society for Cardiac Surgeons [ 5 ]. Meanwhile, Hussain et al [ 6 ] suggested a service system for providing urgent and emergency cardiac surgery for all of London, focusing on maintaining a Covid-free in-hospital environment.…”
Section: Resultsmentioning
confidence: 99%
“…>Local extracorporeal membrane oxygenation (ECMO) protocols for both Covid-19 and non-Covid-19 patients should be developed [ 4 , 5 , 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the findings of other studies performed during the pandemic and may be attributed to several factors. Another significant finding of this study was the higher rate of readmissions in group B, which may be explained by the recommendation of the Saudi MOH about reducing patients’ length of stay to minimize the risk of infection and virus transmission as the post-infective complication of myocarditis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was recommended that one catheterization laboratory per hospital should be active. As the pandemic progresses, it would appear that these effects are gradually decreasing [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%